Dynamic Monte Carlo simulation of oscillations and pattern formation during the NO+CO reaction on the Pt (100) surface - Alas, S. J. (2006)
Theoretical simulations by a dynamic Monte Carlo method were carried out with respect to the catalytic reduction of NO by CO on the Pt(100) surface. This reaction, when occurring at low pressures and under certain reaction conditions, exhibits different temporal and spatiotemporal behaviors, caused by an adsorbate-induced surface restructuring. The studies herein developed take into account recent experimental evidences concerning the NO+CO reaction on the Rh(111) surface; such experiments have shown that the production of molecular nitrogen occurs preferentially via the formation of an (N–NO)* intermediary species rather than through the conventional N+N recombination step. Sustained, irregular or damped oscillations as well as the formation of cellular structures and turbulent patterns are observed during our Monte Carlo surface reaction analysis.